The Influence of HR Practices on Job Satisfaction in the Delivery of Decentralized Health Services (Case Study at Sawerigading General Hospital, Palopo City - M. Risal; Muh. Yusuf Q; Tira Dewi Bustami (Budapest International Research and Critics University, 2021)
The progress of the service sector, especially in the health sector, is dependent on how good job satisfaction is felt by employees. Good job satisfaction brings a good impact on every service that occurs. The purpose of this study is to determine how the relationship and influence of human resource practices which are categorized into job training, human resource development, work environment and competence on job satisfaction. The results showed that job training, human resource development, work environment and competence had a positive and significant effect on job satisfaction.